2001
DOI: 10.1054/bjoc.2001.1856
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms of bone resorption in breast carcinoma

Abstract: Bone destruction is a major complication of advanced malignant disease. It causes bone pain, pathological fracture and hypercalcaemia. Tumour-associated osteolysis and hypercalcaemia is seen in association with haematological malignancies (e.g. myeloma, lymphoma) and solid tumours, mainly carcinomas, where it may occur both in the presence (e.g. cancer of the lung, breast, thyroid, kidney, etc.) and absence (e.g. cancer of the lung, breast, head and neck, kidney, ovary, etc.) of bone metastases (Mundy, 1991;Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
2
16
0
1
Order By: Relevance
“…It could be safely used in treatment of secondary bone lesions associated with various cancers (31,48,49), including breast cancer, and those associated with other diseases, such as osteoporosis, Paget's disease, and rheumatoid arthritis. Zerumbone suppresses osteoclast formation in vitro in a RANKL-dependent manner as shown in this article.…”
Section: Discussionmentioning
confidence: 99%
“…It could be safely used in treatment of secondary bone lesions associated with various cancers (31,48,49), including breast cancer, and those associated with other diseases, such as osteoporosis, Paget's disease, and rheumatoid arthritis. Zerumbone suppresses osteoclast formation in vitro in a RANKL-dependent manner as shown in this article.…”
Section: Discussionmentioning
confidence: 99%
“…Secreted products of breast cancer cells have been shown to increase the formation of mononuclear phagocyte-osteoclasts. 36 Our results also suggest that the osteolysis associated with mesenchymal tumours may be prevented by agents which inhibit the formation of osteoclasts and bone resorption, such as osteoprotegerin and bisphosphonates.…”
Section: Discussionsupporting
confidence: 59%
“…7,8) Indeed, the molecular crosstalk between osteoblasts and osteoclasts plays a key role in regulating bone metabolism. Although some previous studies have demonstrated the effects of osteoclast activation induced by breast cancer metastasis on the amount of bone, 3,9,10) how it affects the bone microstructure remains uncertain.…”
Section: Introductionmentioning
confidence: 99%